Cut-soiler-constructed residue-filled preferential shallow sub-surface drainage improves the performance of mustard-pearl millet cropping system in saline soils of semi-arid regions - Neha,; Yadav, Gajender; Yadav, Rajender Kumar; Kumar, Ashwani; Rai, Arvind Kumar; Prasad, Govind; Kumar, Satyendra; Narjary, Bhaskar; Onishi, Junya; Omori, Keisuke; Chaudhari, Suresh Kumar (Frontiers in Agronomy, 2024)
Agricultural productivity in semi-arid regions is constrained by soil and groundwater salinity. This study quantified the desalinization potential of cut-soiler-constructed preferential shallow sub-surface drainage (PSSD) and its impact on crop performance in saline agroecologies. The study was conducted at the Indian Council of Agricultural Research (ICAR)-Central Soil Salinity Research Institute, Karnal, India, from 2019-2021. The rice residue-filled PSSD was simulated manually (60 cm depth) in a split-split plot experiment with saline and normal soil under saline water irrigation (4, 8, and 12 dS m-1). Cut-soiler PSSD were constructed in the middle of the lysimeter using rice residue (equivalent to 6 Mg ha-1) as the filling material with an outlet to quantify salt and water outflow. Pearl millet [Pennisetum glaucum L. (R. Br)], variety HHB-197, and mustard (Brassica juncea L.), variety CS-58, were grown in the rainy (Kharif) and winter (Rabi) seasons, respectively. The soil salinity profile decreased by 23.3%-58.5% with cut-soiler PSSD in different soils. The decrease in salinity was associated with increased plant height, dry matter accumulation (DMA), net assimilation rate (NAR), crop growth rate (CGR), relative growth rate (RGR), leaf area (LA), and leaf area Index (LAI) in both crops. The pearl millet and mustard yield increases in the two soil types were 11.6%-43.3% and 26%-36%, respectively using saline water up to 12 dS m-1. This study concludes that cut-soiler PSSD can effectively mitigate salinity stress and utilize saline water at the farm scale in salt-affected semi-arid agro-eco-regions.